Dry matter yield and chemical composition of sorghum cultivars with varying planting density and sowing date - Mahmood, A.; Habib Ullah,; Shahzad, A.N.; Ali, H.; Ahmad, S.; Zia-Ul-Haq, M.; Honermeier, B.; Hasanuzzaman, M. (Universiti Kebangsaan Malaysia, 2013)
This two-year research was carried out to clarify the effect of varying sowing time, planting density and cultivar on the biomass yield and chemical composition of sorghum. The leaf area index of the sorghum plant stand reached a maximal value of 5.0−5.7 at 97 days after sowing (DAS). Cultivar ‘Bovital’ was more productive with respect to the number of tillers per plant as well as per m2. Cultivars had clear impact on most of the quality parameters. Cultivar ‘Goliath’ (Sorghum bicolor × S. bicolor hybrid) had a higher biomass yield than Bovital (S. bicolor × S. sudanense hybrid). Dry matter yield was largely unaffected by the plant density at all sowing times. It was observed that Goliath exhibited higher sugar and neutral detergent fibre, while a greater content of protein was found in Bovital. Plant density had no clear influence on most of the quality parameters.